Religious Tourism Development through Policy Formulation: Synergy of Myth, Tradition, and Entrepreneurial Communication - Subekti, Priyo; Rejeki, Diah Sri; Wada, Ibrahim; Hafiar, Hanny (Nyimak: Journal of Communication, 2025)
Religious tourism is pilgrimages and visits to holy places for religious ceremonies.  Considered a major pilgrimage site, the Tomb of Sheikh Quro in Karawang is visited often for spiritual reasons.  Apart from its intrinsic value, religious travel boosts the local economy and helps small businesses and traders especially.  It generates fresh business prospects, therefore helping nearby towns. The synergy between myths and entrepreneurial communication in maintaining religious tourism is investigated in this paper.  It gathers data by participant observation, in-depth interviews, and surveys using a descriptive approach including quantitative and qualitative data.  Results expose that stories about Sheikh Quro's miracles draw pilgrims and support economic development, especially in small trade, lodging, and transportation. The study emphasizes how religious beliefs and cultural narratives can define entrepreneurial communication.  By involving the local community in the upkeep of Sheikh Quro's Tomb, spiritual relics are kept intact and economic gains are raised.  By means of focused campaigns and outstanding services, strategic communication enables local businesses to maximize pilgrim arrivals, so increasing visitor happiness and tourist sustainability.Keywords: Cultural narrative, Entrepreneurial communication, Local economy, Sustainable tourism, Tourism communication.ABSTRAKWisata religi adalah ziarah dan kunjungan ke tempat-tempat suci untuk upacara keagamaan. Dianggap sebagai situs ziarah utama, Makam Syekh Quro di Karawang sering dikunjungi karena alasan spiritual. Terlepas dari nilai intrinsiknya, perjalanan religius meningkatkan ekonomi lokal dan membantu usaha kecil dan pedagang khususnya. Hal ini menghasilkan prospek bisnis yang segar, sehingga membantu kota-kota di sekitarnya. Sinergi antara mitos dan komunikasi kewirausahaan dalam mempertahankan wisata religi diselidiki dalam makalah ini. Penelitian ini mengumpulkan data melalui observasi partisipan, wawancara mendalam, dan survei dengan menggunakan pendekatan deskriptif termasuk data kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa cerita tentang mukjizat Syekh Quro menarik para peziarah dan mendukung pembangunan ekonomi, terutama dalam perdagangan kecil, penginapan, dan transportasi. Penelitian ini menekankan bagaimana kepercayaan agama dan narasi budaya dapat mendefinisikan komunikasi kewirausahaan. Dengan melibatkan masyarakat setempat dalam pemeliharaan Makam Syekh Quro, peninggalan spiritual tetap terjaga dan keuntungan ekonomi meningkat. Melalui kampanye yang terfokus dan layanan yang luar biasa, komunikasi strategis memungkinkan bisnis lokal untuk memaksimalkan kedatangan peziarah, sehingga meningkatkan kebahagiaan pengunjung dan keberlanjutan wisata.Kata Kunci:  Ekonomi lokal, Komunikasi kewirausahaan, Mitos, Pariwisata berkelanjutan, Wisata religi